Peran Pendidikan Kewarganegaraan dalam Melestarikan Cita-cita Demokrasi - Fadilah Balqis; Anwar Sidik (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
The background of this research is driven by the vital importance of strengthening democratic values amidst the challenges of globalization and digitalization, which have begun to erode civic consciousness among the younger generation, particularly in the Pasir Pengaraian region. As the flow of unfiltered information increases, there are significant concerns regarding the decline in understanding the essence of participatory democracy and civic ethics. The primary objective of this study is to analyze in depth the strategic role of civic education as a means to preserve democratic ideals and to identify supporting and inhibiting factors in its implementation within higher education environments. The research method employed is a descriptive qualitative approach, utilizing observations and in-depth interviews with students and academics in Pasir Pengaraian to obtain an objective overview of local political dynamics. Research findings indicate that civic education serves effectively as a pillar of political literacy capable of transforming student perceptions from apathy to active participation, while also serving as a medium for character building that respects diversity of opinion. Furthermore, the integration of local Pasir Pengaraian values with the national curriculum is proven to increase the relevance and absorption of democratic material among students.